Rancang Bangun Aplikasi Persewaan Buku Berbasis Desktop Pada Kabuki Surabaya - Restiawan, Adhitya Bhima; Sutanto, Teguh; Shintawati, Rahayu Arya (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Kabuki Surabaya is a small books rental that aim to help kids in the neighborhood to have access to books. The rental is offering not only to rent books but also selling books. Lately the rental gain so much customer that makes the owner become so busy that they cant oversee the rental and sometimes there is a long queue of customers because of manual proccesses, that makes the customer feel uneasy. This research aim to develop a software based on the problem that the rental has. A software that can help to record transactions proccesses faster that manual so there wont be a long queue of customer again, then the records is stored in database so it can be used to provide some information about rental. Not only that, the software can be used to manage the stock of books that the rental have. This software is developed by using waterfall model of System Development Life Cycle (SDLC) so the risk can be minimal because all the requirement are defined at the beginning of development. In regards of developing the software more, an idea about safety stock is good for future update.